Food for thought: obstacles to menu labelling in restaurants and cafeterias. Issue 12 (3rd August 2015) - Thomas, Erica
Abstract: Menu labelling is recommended as a policy intervention to reduce obesity and diet-related disease. The present commentary considers the many challenges the restaurant industry faces in providing nutrition information on its menus. Barriers include lack of nutrition expertise, time, cost, availability of nutrition information for exotic ingredients, ability to provide accurate nutrition information, libel risk, customer dissatisfaction, limited space on the menu, menu variations, loss of flexibility in changing the menu, staff training and resistance of employees to change current practice. Health promotion specialists and academics involved in fieldwork must help restaurateurs find solutions to these barriers for menu labelling interventions to be widely implemented and successful. Practical support for small independent restaurants such as free or subsidised nutrition analysis, nutrition training for staff and menu design may also be necessary to encourage voluntary participation.